Higher plants as bioindicators of sulphur dioxide emissions in urban environments. (Environmental monitoring and assessment, 2005)
The evaluation of certain vascular plants that grow in the city of Madrid as biomonitors of SO(2) air pollution in urban environments has been carried out. Total concentration of sulphur in leaves of the chosen higher plants as well as other parameters in close relation to this contaminant (visible injury symptoms, chlorophyll a- and b-content and peroxidase activity) have been determined in order to study the spatial distribution and temporal changes in SO(2) deposition. Results obtained show that coniferous species such as Pinus pinea, were more sensitive to SO(2) atmospheric concentration than leafy species as Quercux ilex subspecies ballota and, in the same way, bush species, such as Pyracantha coccinea and Nerium oleander, were more sensitive than wooded species, such as Cedrus deodara and Pinus pinea, respectively. There is a higher accumulation of sulphur in vegetable species located near highways and dense traffic incidence roads and near areas with high density of population. The minimum values for accumulation of SO(2) were registered in winter and spring seasons (from January to April) due to the vegetative stop; while maximum values are obtained during the summer season (from June to September), due to the stoma opening. The highest increments in sulphur concentration, calculated as the difference between two consecutive months, are obtained in May and June for all considered species except for Cedrus deodara and Pyracantha coccinea, both species have few seasonal changes during the whole year. Some species are more sensitive to natural washing than others, showing a decrease in sulphur concentration after rainfall periods.